2010
DOI: 10.2754/avb201079030385
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Diet Supplemented with Natural Humic Compounds and Sodium Humate on Performance and Selected Metabolic Variables in Broiler Chickens

Abstract: The effect of humic substances from different sources on the performance and selected biochemical indicators was studied in 150 one-day-old broiler chickens (Ross 308) divided into control (C) and two tested groups (n = 50). Chickens of tested groups were fed diets supplemented with natural humic compounds (group HS) and sodium humate (group HNa) at amounts of 5 g·kg -1 of feeds in phase 1 and 7 g·kg -1 of feeds in phases 2 and 3 of the fattening period. Higher final body weights (not significant) were observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 14 publications
1
19
1
Order By: Relevance
“…Serum mineral levels (Ca, P, Mg and Fe) were not affected by ZnO + HNa treatments. HS appear to have metal-chelating effects and were reported to reduce levels of serum minerals in broilers (Rath et al 2006;Celik et al 2008;Samudovska and Demeterova 2010) and rabbits (Mista et al 2012), although this effect was not observed with HNa in weaned piglets (Trckova et al 2015). Significantly higher Zn levels in the serum of the ZnO 2.5 group reflected the higher Zn dietary intake in the group.…”
Section: Clinical Biochemical and Haematological Indicators Of Healtmentioning
confidence: 94%
See 1 more Smart Citation
“…Serum mineral levels (Ca, P, Mg and Fe) were not affected by ZnO + HNa treatments. HS appear to have metal-chelating effects and were reported to reduce levels of serum minerals in broilers (Rath et al 2006;Celik et al 2008;Samudovska and Demeterova 2010) and rabbits (Mista et al 2012), although this effect was not observed with HNa in weaned piglets (Trckova et al 2015). Significantly higher Zn levels in the serum of the ZnO 2.5 group reflected the higher Zn dietary intake in the group.…”
Section: Clinical Biochemical and Haematological Indicators Of Healtmentioning
confidence: 94%
“…This is in accordance with Zhang et al (2014), who reported a dosedependent increase in TGC with supplementation of dietary Zn. On the other hand, HS were 191.5 ± 0.03 286.8 ± 0.03 249.5 ± 0.04 271.9 ± 0.04 ** ** ** ** ns ns ns Feed intake (g/pig/day) 453.5 ± 287.5 500.9 ± 327.5 495.8 ± 324.6 492.4 ± 304.8 ns described to decrease serum TGC and cholesterol in animals (Samudovska and Demeterova 2010;Mista et al 2012;Ozturk et al 2012). In our study, partial substitution of ZnO by HNa in feed resulted in significantly lower serum TGC in comparison with ZnO 2.5, but this was not observed when HNa was supplemented in water.…”
Section: Clinical Biochemical and Haematological Indicators Of Healtmentioning
confidence: 96%
“…HS were reported to reduce serum minerals (P, Ca, Mg and Fe) in broilers (Rath et al 2006;Celik et al 2008;Demeterova et al 2009;Samudovska and Demeterova 2010), and rabbits (Mista et al 2012). A potential metal-chelating effect might be exerted by many reactive functional groups located in the structures of HS (Rath et al 2006).…”
Section: Haematological and Serum Biochemical Profilementioning
confidence: 99%
“…HS were described to decrease serum triacylglycerols and cholesterol levels in animals (Herzig et al, 2009;Samudovska and Demeterova 2010;Mista et al 2012;Ozturk et al 2012). After three weeks of HNa dietary treatment we observed only slightly (non-sig- 1 C = control with no supplementation; ZnO2.5 = supplemented with high prophylactic dose of ZnO (2.5 g/kg diet); HNa + ZnO1.7, HNa + ZnO1.5, HNa + ZnO1.0 = supplemented with HNa (20.0 g/kg diet) and 1.7, 1.5 and 1.0 g ZnO/kg diet, respectively The individual pig served as the experimental unit.…”
Section: Haematological and Serum Biochemical Profilementioning
confidence: 99%
“…However, this continuous use of antibiotics resulted in development of drug-resistant bacteria, drug residues in the body of animals, and imbalance of normal microflora. Different natural substances, such as probiotics, prebiotics (Wang et al, 2016), phytobiotics (Abd El-Hakim et al, 2009;Hassan et al, 2015), enzymes (Ao et al, 2009;Benţea et al, 2010), humic substances (Šamudovská & Demeterová, 2010), and acidifiers (Byrd et al, 2001;Eftekhari et al, 2015), can be used as feed additives and may improve health of animals, reduce microbial pathogens (e.g. Escherichia coli, Salmonella or Campylobacter) without the use of antibiotics, and enhance nutrition digestibility for better performance and to decrease the accumulation of ammonia in premises.…”
Section: Introductionmentioning
confidence: 99%